ASPEK HUKUM DALAM PENYALURAN KREDIT USAHA RAKYAT (KUR) - Nurhotia Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2018)
Based on data from the Statistics Agency in 2013 that the Open Unemployment Rate (TPT) reached 6.17%. Unlike the case with TPT in February 2014 it reached 5.70%. Thus, it seems that TPT in Indonesia is currently still high. For this reason, the government's efforts to overcome these problems are very important. Such as opening jobs that can absorb more workers. Because seeing the TPT data there was a shift between 2013 and 2014 due to the increase in employment, especially in the trade sector